2010
DOI: 10.1093/poq/nfp074
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Permissiveness Toward Euthanasia: Religiosity, Slippery Slope, Autonomy, and Death with Dignity

Abstract: This study explores explanations for the approval of euthanasia by assessing differences among individuals and countries, using four main arguments used by opponents and proponents in the public debate over euthanasia. We performed multilevel analysis on data from thirtythree countries, obtained from the European Values Study 1999/2000 and the World Values Survey 2000; we enriched these data with countryspecific information. First, our results supported the hypothesis based on the religion argument: religious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
83
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(105 citation statements)
references
References 16 publications
12
83
6
2
Order By: Relevance
“…Second, the finding that the experience of physical pain is an important mediator for the level of support for euthanasia is in line with Verbakel and Jaspers' (2010) argument that the pain factor is an important anchor for the death with dignity hypothesis and is responsible for raising awareness of the euthanasia debate from the individual level to the national level. That is, while the fear of unbearable pain and suffering might be a result of someone's personal experience, the argument is that if enough people experience or observe much suffering, then the issue of pain and suffering becomes national and the death with dignity argument becomes more significant.…”
Section: Discussionsupporting
confidence: 71%
“…Second, the finding that the experience of physical pain is an important mediator for the level of support for euthanasia is in line with Verbakel and Jaspers' (2010) argument that the pain factor is an important anchor for the death with dignity hypothesis and is responsible for raising awareness of the euthanasia debate from the individual level to the national level. That is, while the fear of unbearable pain and suffering might be a result of someone's personal experience, the argument is that if enough people experience or observe much suffering, then the issue of pain and suffering becomes national and the death with dignity argument becomes more significant.…”
Section: Discussionsupporting
confidence: 71%
“…Kelley and De Graaf, 1997;Verbakel and Jaspers, 2010). First, religious institutions such as the church play an important role in the public debate about moral issues such as homosexuality since they spread their messages through major institutional vehicles like the media, education and politics (Moore and Vanneman, 2003).…”
Section: Religiositymentioning
confidence: 99%
“…One comparative study of public attitudes published in 2010 performed multilevel analysis on data obtained from the European Values Study 1999/2000 and the World Values Survey 2000. [31][32][33] The authors found that religiosity alone did not inform the public's views on euthanasia (although it was again significant). The study reported that some religious denominations had more favourable attitudes to euthanasia (Protestant more favourable than Catholic, in turn more favourable than Muslim).…”
Section: Is Religiosity the Only Variable Influencing Doctors' Attitumentioning
confidence: 99%
“…increased use over time in vulnerable groups) were less likely to favour euthanasia. 31 Thus far, these other influences have not been identified as statistically significant in research cohorts of UK doctors, but perhaps some will be identified as more research is done. A systematic review of US physican's attitudes towards AVE and PAS published in 2005 collected figures relating to support for assisted dying and willingness to participate, but did not collect data relating to doctors' reasons for supporting or not supporting assisted dying.…”
Section: Is Religiosity the Only Variable Influencing Doctors' Attitumentioning
confidence: 99%